Geometry and topology of submanifolds and currents : 2013 Midwest Geometry Conference (MGC XIX), October 19, 2013, Oklahoma State University, Stillwater, OK : 2012 Midwest Geometry Conference (MGC XVIII), May 12-13, 2012, University of Oklahoma, Norman, OK - Midwest Geometry Conference; Li, Weiping; Wei, Shihshu Walter (Contemporary mathematics, 2015)
The papers in this volume are mainly from the 2013 Midwest Geometry Conference, held October 19, 2013, at Oklahoma State University, Stillwater, OK, and partly from the 2012 Midwest Geometry Conference, held May 12-13, 2012, at the University of Oklahoma, Norman, OK.The papers cover recent results on geometry and topology of submanifolds. On the topology side, topics include Plateau problems, Voevodsky's motivic cohomology, Reidemeister zeta function and systolic inequality, and freedom in 2- and 3-dimensional manifolds. On the geometry side, the authors discuss classifying isoparametric hypersurfaces and review Hartogs triangle, finite volume flows, nonexistence of stable $p$-currents, and a generalized Bernstein type problem. The authors also show that the interaction between topology and geometry is a key to deeply understanding topological invariants and the geometric problems.